Report on the 2011 Scientific Congress on Martial Arts and Combat Sports - Bruno Avelar-Rosa (Universidad de León, 2012)
The text resumes the communications and posters presented at the 2011 Scientific Congress on Martial Arts and Combat Sports (2011 SCMACS), held on 13, 14 and 15 May 2011, in the Polytechnic Institute of Viseu (Portugal). In an environment characterized by a significant international presence, a total of 36 communications and 25 posters were exposed, organized in eight sessions: 1) Study object, research and systematic of martial arts and combat sports (MA&CS); 2) Pedagogical and didactics dimension on MA&CS; 3) Physical dimensions on MA&CS; 4) Physical and technical dimensions on MA&CS; 5) Psychological and tactical dimensions on MA&CS; 6) Socio- cultural dimensions on MA&CS; 7) Socio-cultural and philosophical dimensions on MA&CS; and, 8) Posters. A formal meeting of the International Martial Arts and Combat Sports Scientific Society (IMACSSS) also took place as an extraordinary event. The results of the congress gave us the possibility for observing the growing interest of the academy in this particular subject, as the evident development of an international network.